2020
DOI: 10.1111/head.13971
|View full text |Cite
|
Sign up to set email alerts
|

Music Modulates Awake Bruxism in Chronic Painful Temporomandibular Disorders

Abstract: Objective In this experimental study, we aimed to determine whether guided music listening (GML) – a music intervention based on models of mood mediation and attention modulation – modulates masticatory muscle activity and awake bruxism in subjects with chronic painful muscular temporomandibular disorders (TMD myalgia, mTMD), a condition causing a significant burden to patients, their families, and healthcare systems. Background Awake bruxism – a stress behavior characterized by clenching of the teeth – is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Stress has a role as a contributing factor for AB 12–15 . Tooth clenching induced by guided music listening increased when listening to stressful music 16 . However, the changes in tooth clenching after listening to stressful music were different between high and low parafunctional groups 17 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Stress has a role as a contributing factor for AB 12–15 . Tooth clenching induced by guided music listening increased when listening to stressful music 16 . However, the changes in tooth clenching after listening to stressful music were different between high and low parafunctional groups 17 .…”
Section: Discussionmentioning
confidence: 98%
“…[12][13][14][15] Tooth clenching induced by guided music listening increased when listening to stressful music. 16 However, the changes in tooth clenching after listening to stressful music were different between high and low parafunctional groups. 17 AB would play a part in stress coping that may differ between individuals.…”
Section: % 100%mentioning
confidence: 97%
“…There is evidence that awake‐bruxism plays a crucial role in the onset and maintenance of myogenic temporomandibular disorders (mTMD), which are characterized primarily by spontaneous pain or pain associated with jaw function (Schiffman et al, 2014; Slade et al, 2016). Importantly, experimental interventions aiming at improving mood by reducing stress and anxiety have been shown to modulate (i.e., increase or decrease) awake bruxism based on the emotional valence of the stimulus (Imbriglio et al, 2020), and that this effect is present in individuals with chronic mTMD but not healthy controls. Therefore, it is highly probable that amygdala plays an important role in modulating jaw motor function in individuals with chronic mTMD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patients with TMD seem to be associated with increased activity in brain areas involved in emotional processing (Weissman-Fogel et al, 2011), suggesting that individuals with this pathology may be more sensitive to music. Among the different technics that can be used for TMD, Imbriglio et al recently demonstrated if adequate music is selected, passive music listening might have positive effects in TMD (Imbriglio et al, 2020). Interestingly, there is evidence of a link between auditory and motor systems in the brain (Chen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%